Ecological Economics and Post-Normal Science Amid Today’s Challenges - García Sánchez, Daniela (2025)
This essay reflects on some of the philosophical and methodological positions of ecological economics inspired by post-normal science for addressing complex problems. The objective is to discuss its continued relevance in addressing current challenges, including marine exploitation and rapid urbanization. It reviews multi-criteria analysis (MCA) and deliberative processes, considering their philosophical positions, characteristics, and applications. Under certain conditions, MCA offers advantages over cost-benefit analysis (CBA), which is the most common method, including providing a framework for more participatory and deliberate processes. This will depend on the techniques used to achieve adequate participation from interested parties, including the most vulnerable, promoting bidirectional communication between internal and external actors, and giving a voice to the community in the definition of their development.